Pengaruh Pelaksanaan Kegiatan IMTAQ Terhadap Tingkat Keimanan Dan Ketakwaan Siswa SDN Galang Bulan - Hesty Febrian Widyana; Fitriani Fitriani; Lalu Sumardi; Dadi Setiadi (Pascasarjana Universitas Qomaruddin, 2025)
The rapid development of the digital era presents new challenges to the cultivation of religious values among elementary school students, highlighting the need for structured programs that strengthen their spiritual character. This study aims to examine the influence of the IMTAQ (Faith and Piety) program on students’ levels of faith and piety at SDN Galang Bulan, Central Lombok. A quantitative ex post facto design was employed, involving 91 Muslim students from grades IV, V, and VI. Data were collected using Likert-scale questionnaires that measured the implementation of the IMTAQ program and students’ levels of faith and piety. The findings indicate that the IMTAQ program was implemented in the “good” category (mean = 3.23), and students’ faith and piety levels also fell within the “good” category (mean = 3.20). Statistical analysis revealed a significant positive correlation between the implementation of IMTAQ and students’ faith and piety (r = 0.678, p < 0.05), with a coefficient of determination of R² = 0.46, indicating that 46% of the variance in faith and piety is explained by the IMTAQ program. This study concludes that consistent, structured, and value-oriented IMTAQ activities play a substantial role in fostering students’ spiritual behavior. The implications of this research suggest that schools should enhance the variety and quality of IMTAQ activities while encouraging greater involvement from teachers and parents to optimize religious character development among students.